Pengaruh Gaya Kepemimpinan Trasformasional Dan Kompensasi Serta Komunikasi Terhadap Kinerja Aparatur Desa Di Desa Mulyorejo Kecamatan Silo Kabupaten Jember - Nurianto, Nanang Eko; Setyowati, Trias; Umamy, Septi Holisa (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of Transformational Leadership Style, Compensation, and Communication on the Performance of Village Apparatus in Mulyorejo Village, Silo Sub- district, Jember Regency. The background of this research is based on the suboptimal performance evaluation of the village apparatus, characterized by low work enthusiasm, lack of job satisfaction, and weak communication among employees. This study uses an explanatory method with a quantitative approach. Primary data were obtained through questionnaires, interviews, and direct observation of the village apparatus, while secondary data were collected from documents, journals, and relevant reports. The results show that the variables Transformational Leadership Style (X₁) and Compensation (X₂) have a significant influence on Employee Performance (Y), while the Communication variable (X₃) does not have a significant partial influence. Leaders who can be role models, provide inspiration, and support individual development have proven to improve work motivation, collaboration, and employee loyalty. On the other hand, a fair compensation system such as a fixed salary, bonuses, and social security also contributes to performance by creating a sense of security and enhancing work motivation. Conversely, the analysis indicates that although communication plays an important role in an organization, the quality of communication among the village apparatus is not yet strong enough to significantly improve performance.